EDUCATING TOMORROW: LESSONS FROM MANAGING GIRLS’ EDUCATION IN AFRICA (Authors: Angela Thody & Eleanor Stella Mkaabwe) - Garrow, Stephanie (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2000)
ANGELA THODY & ELEANOR STELLA MKAABWE. Educating Tomorrow: Lessons From Managing Girls’ Education in Africa. Cape Town. South Africa: Juta (2000). 266 pp. R99.00. (ISBN 0 7021 5209 9).